The effect of interfacial phenomena on gas solubility measurements in molten salts - McFarlane, Joanna; Andrews, Hunter B.; McAlister, Abbey L.; Moon, Jisue; Robb, Kevin R.; Weber, Charles F.; Ballard, Andrew (Frontiers in Energy Research, 2023)
The behavior of fission gases in molten fuel salt reactors governs activity transport from the reactor and can also affect the performance of the reactor itself. The gas solubility can be described thermodynamically by Henry’s law. However, the coupling of the condensed and gas phases depends on the interfacial area, which is difficult to measure or even to estimate. Surfaces of materials in the reactor will include disperse phases in the salt and porosity within the structural materials, covering a range of compositions and sizes. These attributes can affect measurements of fundamental properties such as gas solubility. Methods to obtain gas solubility, surface tension, interfacial energies, and bubble gas transport are reviewed. Recent data from manometric experiments are interpreted based on xenon sorption onto salt-wetted quartz.